PENGARUH PENGAWASAN PIMPINAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI UPT PENGEMBANGAN TANAMAN OBAT, NANGGUNG KABUPATEN BOGORPENGARUH PENGAWASAN PIMPINAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI UPT PENGEMBANGAN TANAMAN OBAT, NANGGUNG KABUPATEN BOGOR - Pratama Santosa, Angga; ., Aminudin (Economicus, 2018)
This study aims to identify the effect of supervision of the leadership on employee productivity simultaneously at UPT Development of Medicinal Plants Nanggung District Bogor Regency. The research type is explanatory research which analyzed with quantitative approach including Correlation Coefficient (KK), Coefficient of Determination (KD), Simple Linear Regression and Hypothesis Test. The number of samples was 32 respondents with purposive sampling. Data collection techniques through literature study, questionnaire distribution, and observation. Likert scale is used for Questionnaire question. Leadership supervision as independent variable with indicator: work standard setting, measurement of work result, correction action, and feedback. Employee productivity as a dependent variable, with indicators: quantity, quality, timeliness and motivation. Hypothesis test results showed the positive and significant influence of supervision of the leadership to employee work poduktivitas. It means, if the supervision of the leadership increases then it will be followed by increased employee productivity. The result of statistical calculation of Coefficient of Determination (r2) or R square and Simple Linear Regression equation showed a differentiator between supervisory variables of leadership with productivity variables and any increase in the value of supervisory leadership will increase the influence of work productivity of workers.